Impact of cinnamon oil-enrichment on microbial spoilage of fresh produce - Tzortzakis, Nikos G. (My University, 2009)
Cinnamon (Cinnamomum zeylanicum L.) oil (ranging between 25 and 500 ppm) was tested for antifungal activity against Colletotrichum coccodes, Botrytis cinerea, Cladosporium herbarum, Rhizopus stolonifer and Aspergillus niger in vitro. Oil-enrichment resulted in significant (P < 0.05) reduction on subsequent colony development for the examined pathogens. Fungal spore production inhibited up to 63% at 25 ppm of cinnamon oil concentration when compared with equivalent plates stored in ambient air. In the highest oil concentration (500 ppm) employed, fungal sporulation (except for B. cinerea) was completely retarded. In vitro, cinnamon oil reduced spore germination and germ tube length in C. coccodes, B. cinerea, C. herbarum and R. stolonifer with the effects were dependent on oil concentration. However, cinnamon oil (up to 100 ppm) accelerated spore germination for A. niger. Wound-inoculated pepper fruit accelerated B. cinerea and C. coccodes development following 3 days vapour exposure to cinnamon, and this effect was not persisted for longer exposure but no differences observed for tomato fruit. Pre-exposing tomato fruit to 500 ppm cinnamon vapours for 3 days, and then inoculated with fungi, reduced B. cinerea and C. coccodes lesion development. At the present, trials is currently focussing on the mechanisms underlying the impacts of essential oil volatiles on disease development with a major contribution to limiting the spread of the pathogen by lowering the spore load in the storage/transit atmospheres as well as the use of essential oil as an alternative food preservative. Industrial relevance: The data presented in this work suggest that the use of pure cinnamon essential oil is an innovative and useful tool as alternative to the use of synthetic fungicides or other sanitation techniques in storage/packaging. Oil enrichment may reduce disease development with a major contribution to limiting the spread of the pathogen by lowering the spore load (spore production) in the storage/transit atmospheres as well as the use of essential oil as an alternative food preservative. The effectiveness (oil concentration) of the oil depends on the target pathogen. The effects of natural compounds on individual microorganisms (fungi and bacteria), both responsible for spoilage and food-borne pathogens, as well as the minimum concentration to gain effectiveness without affecting fresh produce quality and storage deserve further research. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; Cinnamon; Essential oils; Fresh produce; Fungal growth